A new hybrid of Tectaria (Tectariaceae) from southern China - Zhao, Hui-Guo; Dong, Shi-Yong (Phytotaxa, 2016)
A new natural hybrid, Tectaria × hongkongensis (Tectariaceae), is described and illustrated from Hong Kong, China. It is a sterile hybrid supported by the abortive spores and cytological data [2n = 120 (3x)]. This hybrid is morphologically somewhat similar to T. zeilanica in the small size of plants, strongly dimorphic leaves, the shape of sterile fronds, and acrostichoid sporangia. Molecular data indicate its maternal parent is probably T. harlandii. Tectaria × hongkongensis is the first hybrid confirmed by morphological and cytological evidence in East Asia.